Learning Strategies Through Storytelling For Increase Tolerance Attitudes Of Buddhist Children Aged 4-6 Years In Cibinong - Susijati Susijati; Tisya Permatasari; Astri Chintya Astana (FKIP, Universitas Palangka Raya, 2022)
Storytelling is a powerful strategy in helping children build their comprehension, language skills, and imagination. Stories bring to life the world of children's imagination and help them understand abstract concepts. Through stories, children can learn about the values, characters, and various experiences that shape their understanding of the world. Storytelling, be expected that it can develop tolerance in Buddhist children aged 4-6 years. Through the stories contained in the Khudaka Nikaya-Jataka, the tenth book containing the story of the past life of the Great Master Buddha. From the story retold by the school teacher or Sunday school teacher, it is hoped that Buddhist children aged 4-6 years can develop with good morals and behavior.The results of research by applying the storytelling method make children able to understand the parables of popular Buddhist stories such as the story of a chatty turtle. The meaning of the story is that we must learn to say words that only bring benefits.